Effect of plasma treatment on the release kinetics of a chemotherapy drug from biodegradable polyester films and polyester urethane films. Issue 3 (11th February 2018) - Stloukal, Petr; Novák, Igor; Mičušík, Matej; Procházka, Michal; Kucharczyk, Pavel; Chodák, Ivan; Lehocký, Marian; Sedlařík, Vladimír
ABSTRACT: Investigation was made into the effect of plasma treatment on the release kinetics of the drug Temozolomide (TMZ) from thin, biodegradable polyester films, comprising polylactic acid (PLA) and polyester urethane. The authors utilized two systems to achieve this, the first being diffuse coplanar surface barrier discharge, applying air as the gaseous medium, while the other involved capacitively coupled radio frequency discharge plasma under an argon atmosphere with hexamethyldisiloxane. Results showed that both forms of plasma treatment positively reduced the undesirable burst effect and benefited the release rate of TMZ. The hydrolytic degradability of the materials was slightly enhanced following hydrophilization, whereas the same diminished after hydrophobization had taken place. This was especially true for PLA due to modification of its wettability. GRAPHICAL ABSTRACT: